2010
DOI: 10.1002/smi.1314
|View full text |Cite
|
Sign up to set email alerts
|

Work‐related dimensions and job stress: the moderating effect of coping strategies

Abstract: The aim of this paper is to examine the moderating effect of coping strategies on the relationship between workrelated dimensions (i.e. work routinization, role clarity, relationships with others and promotional opportunity) and job stress. For the study, a convenience sample of 385 white-collar employees, full-time employed in various types of private sector organizations, belong to different industries and ranked at different levels within the organizations responded. The factor analysis led to identify four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 62 publications
2
25
0
7
Order By: Relevance
“…Although previous work is limited, the existing empirical evidence indicates that promotional or career advancement opportunities are related to various workrelated attitudes and behaviours, such as job satisfaction (Ellickson, 2002), turnover intentions (Stahl, Chua, Acliguiri, Cerdin, & Taniguchi, 2009), and job stress (Wickramasinghe, 2010;Yang, Che, & Spector, 2008). Further, consistent with social exchange theory and the norm of reciprocity, we speculate that promotional opportunities will enhance knowledge sharing behaviour because by doing so the employees can return the "favor" to the organisation.…”
Section: Perceived Promotional Opportunitiessupporting
confidence: 67%
See 2 more Smart Citations
“…Although previous work is limited, the existing empirical evidence indicates that promotional or career advancement opportunities are related to various workrelated attitudes and behaviours, such as job satisfaction (Ellickson, 2002), turnover intentions (Stahl, Chua, Acliguiri, Cerdin, & Taniguchi, 2009), and job stress (Wickramasinghe, 2010;Yang, Che, & Spector, 2008). Further, consistent with social exchange theory and the norm of reciprocity, we speculate that promotional opportunities will enhance knowledge sharing behaviour because by doing so the employees can return the "favor" to the organisation.…”
Section: Perceived Promotional Opportunitiessupporting
confidence: 67%
“…When employees feel that their job is stable, the feeling of being at ease is likely to encourage them to learn new things at work. Studies have found that reduced stress is associated with positive work behaviour and well-being (Wickramasinghe, 2010;Yang et al, 2008). The higher the perceived employability, the more likely employees will learn from others to further enrich their capital reservoir.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Role clarity has been identified as important to job satisfaction (Cowin, Johnson, Craven, & Marsh, 2008;Gulliver, Towell, & Peck, 2003;Jones, Smith, & Johnston, 2005;Nelson & Felgen, 2015;Wickramasinghe, 2010).…”
Section: Claritymentioning
confidence: 99%
“…Ahmad et al (2011) y Chandra y Sharma (2010) identificaron como fuentes de estrés en las empresas públi-cas el contenido de trabajo, la falta de reconocimiento, las relaciones interpersonales, la sobrecarga de trabajo y la falta de oportunidades de carrera. Sin embargo, estos mismo estresores, con excepción de la falta de oportunidades de carrera, también fueron obtenidos por Sankpal et al (2010) y Wickramasinghe (2010) en sus estudios con empresas privadas.…”
Section: El Estrés Laboral Y El Sector De La Organizaciónunclassified